PELATIHAN NIK COLOR SOFTWARE EFECT PRO DALAM MENINGKATKAN KEMAMPUAN FOTOGRAFER - Supri Hartanto; Septian Aji Permana (Universitas PGRI Yogyakarta, 2020)
The purpose of this service is to improve the photographer's post-processing capabilities based on Photoshop and Nik Color Pro software in optimizing the results of the photos. This workshop method by providing integrated training from exposure to the need for entrepreneurship studies, understanding of the composition of photography, the practice of shooting and training in the use of nik colour pro software in the post-processing process of work through editing. Assistance is also needed in evaluating the results of photography to produce better work. The conclusions of this paper (1) Community service activities can improve the skills of photographers in opening creative economic opportunities. (2) The intensive training system with direct practice in the field, the guidance of shooting techniques, the direct editing practice of the Nik Color Software Effect Pro training turned out to be effectively applied.